2013
DOI: 10.7863/jum.2013.32.3.475
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Acoustic Cavitation in the Presence of Gold Nanoparticles on a Colon Tumor Model

Abstract: Acoustic cavitation in the presence of gold nanoparticles and intense pulsed light has been introduced as a new way for improving therapeutic effects on tumors by reducing the relative tumor volume and increasing the cumulative survival fraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 29 publications
0
50
0
1
Order By: Relevance
“…A recent study [106] on gold NPs, functionalized with PEG and folic acid and activated with ultrasound, showed a promising reduction in cancer cells growth, accompanied by a significant generation of ROS species. Sazgarnia et al [107] also found that the combination of gold NPs, ultrasound and intense pulsed light was a good strategy to further improve the therapeutic effect on tumors. In fact, the combination of these stimuli can cause a rapid heating and a subsequent vaporization of the surrounding medium, contributing to lower the cavitation pressure [108].…”
Section: Nps Used In the Sonodynamic Therapymentioning
confidence: 99%
“…A recent study [106] on gold NPs, functionalized with PEG and folic acid and activated with ultrasound, showed a promising reduction in cancer cells growth, accompanied by a significant generation of ROS species. Sazgarnia et al [107] also found that the combination of gold NPs, ultrasound and intense pulsed light was a good strategy to further improve the therapeutic effect on tumors. In fact, the combination of these stimuli can cause a rapid heating and a subsequent vaporization of the surrounding medium, contributing to lower the cavitation pressure [108].…”
Section: Nps Used In the Sonodynamic Therapymentioning
confidence: 99%
“…and Sazgarnia et al. demonstrated an enhanced cavitation activity caused by the presence of AuNPs . The intensive local pressure and temperature upsurges, generation of ROS, shock waves, and jet formation are the clear consequences of collapse cavitation, which ultimately cause considerable damage to the tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…The nanoparticles may also act as a nucleation site for cavitation, thus enhancing the ultrasound-induced cavitation. 15,36 The intensive local pressure and temperature upsurges, generation of ROS, shock waves, and jet formation are the clear consequences of collapse cavitation, which ultimately cause considerable damage to the tumor cells. This may be another mechanistic pathway through which AuNPs coupled with ultrasound result in such tumor ablation as observed in the present study.…”
Section: B Mechanical Enhancement Pathway Of Ultrasoundmentioning
confidence: 99%
“…In fact, the nanoparticles mediated drug delivery concept is not the only factor that can enhance SDT [20]. Indeed, the existence of appropriate nanoparticles in the milieu might provide nucleation sites decreasing the cavitation threshold that must be reached through ultrasound exposure [36,37]. Moreover, the ease of the manipulation and loading procedure of our PMMANPs, along with their high stability under forced release conditions, make these nanoparticles particularly attractive for theranostic applications.…”
Section: Discussionmentioning
confidence: 99%